أسلوب الحياة وعلاقته بالاكتئاب لدى الطاقم الطبي بمصلحة الاستعجالات دراسة ميدانية بمستشفى الزهراوي المسيلة - بابش المداني; اشراف: نصيرة لمين (جامعة محمد بوضياف المسيلة, 2025)
هدفت الدراسة الحالية إلى التعرف على الكشف عن العلاقة بين العلاقة بين أسلوب الحياة والاكتئاب لدى الطاقم الطبي لمصلحة الاستعجالات بمستشفى الزهراوي بالمسيلة. وبغية التحقق من فرضيات البحث تم اعتماد المنهج الوصفي من خلال تطبيق مقياسي أساليب الحياة والاكتئاب على عينة من الطاقم الطبي بمصلحة الاستعجالات بمستشفى الزهرواي، تكونت عينة الدراسة من 70 فرد. توصلت الدراسة الحالية إلى النتائج التالية: - لا توجد علاقة بين أسلوب الحياة والاكتئاب لدى الطاقم الطبي لمصلحة الاستعجالات في مستشفى الزهراوي. - مستوى أسلوب الحياة لدى الطاقم الطبي لمصلحة الاستعجالات في مستشفى الزهراوي متوسط. - مستوى أسلوب الحياة لدى الطاقم الطبي لمصلحة الاستعجالات في مستشفى الزهراوي منخفض. - لا توجد فروق ذات دلالة إحصائية في مستوى أسلوب الحياة لدى الطاقم الطبي لمصلحة الاستعجالات تعزى لمتغير الجنس. - لا توجد فروق ذات دلالة إحصائية في أسلوب الحياة لدى الطاقم الطبي لمصلحة الاستعجالات تعزى لمتغير الجنس. الكلمات المفتاحية: أسلوب الحياة، الإكتئاب، الطاقم الطبي. Abstract: The current study aimed to identify and detect the relationship between the relationship between lifestyle and depression among the medical staff of the Department of urgent care at Al-Zahrawi hospital in Mesilla. In order to verify the research hypotheses, the descriptive approach was adopted by applying the measures of lifestyles and depression to a sample of medical staff at the emergency department of Al-zahraway hospital, the study sample consisted of 70 individuals. The current study came to the following conclusions: - There is no relationship between lifestyle and depression among the medical staff in the emergency department at Al-Zahrawi hospital - The standard of lifestyle of the medical staff in the emergency department at Al-Zahrawi hospital is average - The standard of lifestyle of the medical staff in the emergency department at Al-Zahrawi hospital is low - There are no significant differences in the level of lifestyle of medical staff in the interests of urgent care attributable to the sex variant - There are no significant differences in the lifestyle of medical staff in the interests of urgent care attributable to the sex variant Keywords: lifestyle, depression, medical staff..